STATE STANDARDS OF THE REPUBLIC OF BELARUS IN OPTICAL RADIOMETRY - A. V. Galygo; N. V. Hairova; O. V. Tarasova; V. A. Dlugunovich; A. V. Isaevich; S. V. Nikanenka; V. N. Snopko (Приборы и методы измерений)
The results of joint activities of the BelGIM and the Institute of Physics of the NAS of Belarus on the construction and modernization of state standards of the physical units in optical radiometry, as well as the high accuracy measurement facilities for test the energy, temporal, spatial, spectral and polarization characteristics of laser equipments and calibration of devices for measuring the energy characteristics of laser radiation are presented.